The Changing Demographics of Women Living with HIV/AIDS in Southern Alberta from 1982 to 2006 - Liana Hwang; Jesse Raffa; Michael John Gill (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Women account for a growing proportion of HIV infections in Canada. This has implications with respect to prevention, diagnosis and treatment.